Behind the shattered glass - Alexander, Tasha, 1969- (Alexander, Tasha, 1969- Lady Emily mystery., 2013)
Anglemore Park is the ancestral home of Lady Emily Hargreaves husband Colin. But the stately calm of country life is destroyed when their neighbor, the Marquess of Montagu, bursts through the French doors from the garden and falls down dead in front of the shocked gathering. But who has a motive for murdering the young aristocrat? The lovely cousin who was threatened by his engagement, the Oxford friend he falsely accused of cheating, the scheming vicars daughter he shamelessly seduced or the relative no one knew existed who appears to claim the Montagu title? Who is the mysterious woman seen walking with him moments before he was brutally attacked? The trail takes readers into the gilded world of a British manor house and below stairs to the servants who know all the secrets. One familys hidden past and a forbidden passion are the clues to a puzzle only Lady Emily can solve.